Extreme Environments Robotics : Robotics for Emergency Response, Disaster Relief and Resilience /: Robotics for Emergency Response, Disaster Relief and Resilience. ([2017]) - Scanlan, James P (James Patrick), 1958-; (Lecturer), Flynn, David; (Professor of robotics), Lane, David; (Professor of robotics), Richardson, Robert; (Lecturer in flight mechanics), Richardson, Tom; Sóbester, András
No abstract available